2005
DOI: 10.1074/jbc.m505557200
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 Binds Heterogeneous Nuclear Ribonucleoprotein A/B through Its C-terminal Tail

Abstract: TDP-43 is a highly conserved nuclear factor of yet unknown function that binds to ug-repeated sequences and is responsible for cystic fibrosis transmembrane conductance regulator exon 9 splicing inhibition. We have analyzed TDP-43 interactions with other splicing factors and identified the critical regions for the protein/protein recognition events that determine this biological function. We show here that the C-terminal region of TDP-43 is capable of binding directly to several proteins of the heterogeneous n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
202
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 408 publications
(216 citation statements)
references
References 85 publications
7
202
0
Order By: Relevance
“…Studies of TDP-43 complexes with protein and RNA are beginning to provide a clearer understanding of TDP-43 as a component of large RNP complexes (9,41,42). Our observations that CTF transport are dependent on interactions of TDP-43 with RNA and on dynein-mediated MT transport are consistent with its classification as a shuttling RNP protein (12).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Studies of TDP-43 complexes with protein and RNA are beginning to provide a clearer understanding of TDP-43 as a component of large RNP complexes (9,41,42). Our observations that CTF transport are dependent on interactions of TDP-43 with RNA and on dynein-mediated MT transport are consistent with its classification as a shuttling RNP protein (12).…”
Section: Discussionsupporting
confidence: 70%
“…Both RRMs retain nucleic acid binding properties, yet only RRM1 appears essential for RNA splicing (8). The glycine-rich domain is proposed to interact with other hnRNPs to synergistically affect alternative splicing of specific RNA transcripts (9,10). A common feature of shuttling hnRNPs involved in RNA splicing is that their nuclear export is coupled to the export and maturation of mRNA in distinct ribonucleoprotein (RNP) complexes (11,12).…”
mentioning
confidence: 99%
“…In addition, TDP-43 has been implicated in regulation of mRNA biogenesis (9) and shown to be localized to sites of mRNA transcription and processing in neurons (10). As the glycine-rich domain of TDP-43 has been shown to mediate interactions with other heterogeneous nuclear ribonucleoprotein proteins, the low homology of this particular domain may afford a multitude of interactions that allows for diverse biological functions (11).…”
mentioning
confidence: 99%
“…This includes the hnRNPA/B proteins, which are prone to form these structures, especially when exacerbated by disease mutations (Kim et al 2013). Furthermore, hnRNPA2/B1 and hnRNP A1 are capable of binding with TAR DNA binding protein-43 (TDP-43) (Buratti et al, 2005), an important hnRNP identified in inclusion bodies of patients with amyotrophic lateral sclerosis and frontotemperal lobar degeneration (Winton et al, 2008). Note that TDP-43 is composed of an N-terminal region with two RNA recognition motifs and a glycine-rich carboxy terminal domain similar to the squid hnRNPA/B-like proteins, although it does not share primary sequence homology with any that we have identified.…”
Section: Discussionmentioning
confidence: 99%